Lutetium-Specific Prostatic Membrane Antigen (LuPSMA) Treatment for Metastatic Castration-Resistant Prostate Cancer - Paixão, Sanna Verena Moreira; Silva, Carlos Danilo Cardoso Matos (Asian Journal of Health Research, 2024)
Introduction: Cancer is one of the leading causes of death globally, with the majority of cases occurring in low-income countries. There are more than a hundred types, divided into sarcomas and carcinomas. Prostate cancer is the most common cancer among men and is usually asymptomatic. Treatment depends on the stage of the disease and may include surgery, hormone therapy, and radiation therapy. In advanced stages, new treatments such as the radiopharmaceutical LuPSMA are investigated to improve patients' quality of life. Material and Methods: An exploratory-descriptive literature review was conducted using qualitative methods. Data collection spanned 2019–2024, sourcing relevant studies from LILACS, SciELO, and PubMed. Search terms included "Prostate Neoplasms," "Lutetium," and "Positron Emission Tomography combined with Computed Tomography," using both Portuguese and English with the boolean operator "AND." After screening 189 articles for relevance, 30 met the inclusion criteria. Results: Theranostic treatment with LuPSMA demonstrated significant improvements in overall survival and progression-free survival in mCRPC patients. The therapy was well-tolerated, with manageable adverse effects. However, challenges remain in predicting outcomes for patients with low PSMA expression. Conclusion: LuPSMA therapy has shown promise in enhancing survival rates and quality of life for mCRPC patients, offering a well-tolerated alternative to conventional treatments. However, there are uncertainties about the therapeutic response and prognosis in patients with low PSMA expression, indicating the need for further research. The study has contributed to imaging and oncology, offering new perspectives on alternative therapies for metastatic cancer and serving as a basis for future investigations into imaging-guided radionuclide therapies.